Factors associated with loss to clinic among HIV patients not yet known to be eligible for antiretroviral therapy (ART) in Mozambique. Issue 1 (10th June 2013) - Pati, Rituparna; Lahuerta, Maria; Elul, Batya; Okamura, Mie; Alvim, Maria Fernanda; Schackman, Bruce; Bang, Heejung; Fernandes, Rufino; Assan, Americo; Lima, Josue; Nash, Denis; ,
Abstract : Introduction: Retention in HIV care prior to ART initiation is generally felt to be suboptimal, but has not been well‐characterized. Methods: We examined data on 37, 352 adult pre‐ART patients (ART ineligible or unknown eligibility) who enrolled in care during 2005–2008 with >1 clinical visit at 23 clinics in Mozambique. We defined loss to clinic (LTC) as >12 months since the last visit among those not known to have died/transferred. Cox proportional‐hazards models were used to examine factors associated with LTC, accounting for clustering within sites. Results: Of 37, 352 pre‐ART patients, 61% had a CD4 count within three months of enrolment (median CD4: 452, IQR: 345–611). 17, 598 (47.1%) were ART ineligible and 19, 754 (52.9%) were of unknown eligibility status at enrolment because of missing information on CD4 count and/or WHO stage. Kaplan‐Meier estimates for LTC at 12 months were 41% (95% CI: 40.2–41.8) and 48% (95% CI: 47.2–48.8), respectively. Factors associated with LTC among ART ineligible patients included male sex (AHRmen_vs_non‐pregnant women : 1.5; 95% CI: 1.4–1.6) and being pregnant at enrolment (AHRpregnant_vs_non‐pregnant women : 1.3; 95% CI: 1.1–1.5). Older age, more education, higher weight and more advanced WHO stage at enrolment were independently associated with lower risks of LTC. Similar findings were observed among patients whose ART eligibility status was unknown at enrolment. Conclusions: Substantial LTC occurred prior to ART initiation among patients not yet known to be eligible for ART, including nearly half of patients without documented ART eligibility assessment. Interventions are needed to target pre‐ART patients who may be at higher risk for LTC, including pregnant women and patients with less advanced HIV disease.